The Integration of Technology and Management in the Competitiveness of the United States Short Staple Yarn Manufacturing Industry. (9th June 2014) - Tangboonritruthai, Suvalee T.; Oxenham, William; Cassill, Nancy L.; Parrish, Erin D.
Abstract : The purpose of this research was to investigate whether a balance of technology and management could be used in order to sustain a viable United States (US) short staple yarn production industry. The methodology used in this study consisted of primary research comprising two phases. The first phase consisted of interviews with industry executives in order to find out what US yarn manufacturers think are the important factors in maintaining a competitive yarn industry. The second phase was an online survey with industry customers in order to find out why weavers and knitters buy from US manufacturers. Results reveal that US manufacturers have competitive advantages over other countries because of skill level of workforce, variety of products offered, customer relationships, innovation and technology, and product quality. In order to keep these competitive advantages, "technology" and "management" strategies should be implemented. Results also reveal the areas in which the US yarn manufacturers should focus their resources in order to stay competitive or indeed survive.